The branding significance and its relevance to Universiti Sains Islam Malaysia (USIM) / Marina Mamat - Mamat, Marina (Faculty of Business and Management, 2009)
The creation of a strong brand and the deliverance of perceived service quality are premised by employees' ability to deliver on customer expectations. Branding is a phenomenon that allows the individual institution to provide information and images. Branding may also be a promising strategy for improving institutional cooperation. As well, branding efforts may also be a promising way to instigate internal change at a given institution. Last but not least, branding efforts may help higher education institutions to rediscover what they are, and their basic purposes. The branding significance and its relevance to Universiti Sains Islam Malaysia (USIM) is the title for this case study. The issues of this study are; what are the branding problems involve in reaching branding establishment. Management need to identify the problems and factors which influence customer’s preferences towards USIM and how management of USIM practice strategic planning to achieve image and branding. It is important to recognize the ways of solving the problems related with branding. The findings are about what USIM’s practice related to the issues which are institution’s image, competition among other universities, media planning, innovation, and the planning and implementation of integrated marketing communications (IMC). The gap analysis is about the differences between theory and what USIM approach according to the issues. There were recommendations on the gap analysis that have been discovered. In short, by comparing and practicing what the theories stated about branding USIM are able to get better in reaching brand establishment even though they have implement what are the best for their organization appropriate with the situation of the organization itself.